The square of Shaneequa's age six years ago is equal to her age in six years time.
What is her present age?
Really confused and unsure of how to put in algebraic terms. I know the answer, just don't know howto get to it.
Thanks
Let x = her present age.
So, x -6 = her age six years ago
And, x +6 = her age in six years time
(x-6)^2 = x +6
x^2 -12x +36 = x +6
x^2 -12x -x +36 -6 = 0
x^2 -13x +30 = 0
(x -10)(x -3) = 0
x = 10 or 3 years
When x = 10 years,
x -6 = 10 -6 = 4 years, so she is 4 years old six years ago.
When x = 3 years,
x -6 = 3 -6 = -3 years, cannot be. She cannot be -3 years old anytime.
Therefore, she is 10 years old at present. ------------answer.